2016
DOI: 10.1007/s00253-016-7547-z
|View full text |Cite
|
Sign up to set email alerts
|

Applying theories of microbial metabolism for induction of targeted enzyme activity in a methanogenic microbial community at a metabolic steady state

Abstract: Novel enzymes that are stable in diverse conditions are intensively sought because they offer major potential advantages in industrial biotechnology, and microorganisms in extreme environments are key sources of such enzymes. However, most potentially valuable enzymes are currently inaccessible due to the pure culturing problem of microorganisms. Novel metagenomic and metaproteomic techniques that circumvent the need for pure cultures have theoretically provided possibilities to identify all genes and all prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…The recipe was modified a number of times until a final composition was found that enabled the microbial communities to reach metabolic steady state. The reactors and the defined medium is describe in detail in paper I [125]. By changing the chemical composition of the medium over a time period of about five months it allowed the microbial communities to adapt to the changes and maintain a complete and viable biogas producing community.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recipe was modified a number of times until a final composition was found that enabled the microbial communities to reach metabolic steady state. The reactors and the defined medium is describe in detail in paper I [125]. By changing the chemical composition of the medium over a time period of about five months it allowed the microbial communities to adapt to the changes and maintain a complete and viable biogas producing community.…”
Section: Methodsmentioning
confidence: 99%
“…This makes them highly interesting as targets for enzyme discovery. In paper I [125], it was shown that the conditions for an efficient and targeted enzyme discovery by metaproteomics are conceivable. In particular it was shown that it is possible to establish a viable microbial community using a chemically defined medium, which is necessary for the downstream analysis.…”
Section: Metaproteogenomics For Discovery Of Novel Enzymesmentioning
confidence: 99%
“…What is important to note is that a viable microbial community was established, which was maintained at a metabolic steady state, which in turn produced an environment with very low background of extracellular hydrolytic enzymeactivity. By exchanging the substrate during culturing, the community responded measurably to the change by expression of extracellular, hydrolytic enzymes to specifically break down the substrate added, without interference of contaminating substances and proteins that originate from the original habitat (paper I [118]). This is of outstanding importance, because it is usually very difficult in meta-omics projects to identify relevant enzymes or target the production of specific enzymes against the large background of all proteins that are collected.…”
Section: Metaproteogenomics Is a Rather New Technique In The Integratmentioning
confidence: 99%
“…It contains over 40 individual components and was refined several times during this study to allow for the microbial communities to reach a metabolic steady state. Detailed information on the final recipe is given in paper I [118]. The gradual exchange of culturing medium during the experiments resulted in a microbial community in a constructed environment that was eventually free of components and impurities from the original biogas reactor habitats after an operation time of approximately five months.…”
Section: The Construction Of Methanogenic Microbial Communities At Stmentioning
confidence: 99%
See 1 more Smart Citation